2022
DOI: 10.1002/aenm.202104052
|View full text |Cite
|
Sign up to set email alerts
|

Triphasic Metal Oxide Photocatalyst for Reaction Site‐Specific Production of Hydrogen Peroxide from Oxygen Reduction and Water Oxidation

Abstract: The search for photocatalysts allowing the highly active, selective, and stable conversion of molecular oxygen into hydrogen peroxide is of worldwide interest. Here, the authors report the efficient conversion of O2 into H2O2 with ≈100% selectivity and stable cycle stability by a triphasic metal oxide photocatalyst with a cobalt hydroxide carbonate nanosheet phase for water oxidation as well as iron oxide and titanium oxide phases of a core‐shell morphology for charge transfer and oxygen reduction, denoted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The effect of adding 10% isopropyl as a sacrificial agent was also evaluated . The results show that the performance of the system is much higher than that without isopropyl addition (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of adding 10% isopropyl as a sacrificial agent was also evaluated . The results show that the performance of the system is much higher than that without isopropyl addition (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, rational nanostructure design can be applied for heterojunction photocatalysts. Kim et al 147 have reported a triphasic metal oxide photocatalyst for converting water and oxygen into H 2 O 2 with high activity, stability and selectivity. A type II heterojunction was constructed from amorphous TiO 2 and crystallized Fe 3 O 4 with a core-shell morphology on Co 2 (OH) 2 -CO 3 nanosheets, corresponding to visible-to-UV light absorption.…”
Section: Environmental Science: Water Research and Technologymentioning
confidence: 99%
“…Also, H 2 O 2 is expected to grow in importance as a carbon-neutral high-energy liquid energy carrier (60 wt.% H 2 O 2 aqueous yields an energy density of about 3.0 MJ L −1 ) in terms of its storability and transportability 5 , 6 . Traditional anthraquinone process for H 2 O 2 production needs high energy consumption and yields a lot of chemical waste 7 , 8 . Particulate photocatalysis, namely the catalytic conversion of O 2 and water by irradiating solar energy on semiconductors, has emerged as a sustainable strategy for H 2 O 2 production 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%